(untitled) (Bangladesh Journal of Medical Science, 2014)
A 30 years old female patient presented us with pain, restricted movement of hip and difficulty of walking. She had past history of taking oral Steroid for 6 months for gaining weight. Radiological examination revealed bilateral avascular necrosis of hips with advanced osteoarthritic changes. The patient had sequential Total hip replacement on both sides in 6 weeks interval. Post operatively she was uneventful and after proper exercise and physiotherapy she is maintaining her daily household activities smoothly. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18304 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.205-208